Pathogenicity and Host Range of Xanthomonas campestris pv. campestris – Incitant of Black Rot of Crucifers - Bhat1 and S. A. Mir1, Nazir A. Bhat1*, Nusrath Syeed2, K. A. (Journal of Phytology, 2010)
Black rot caused by Xanthomonas campestris pv. campestris (Pammel) Dowson is a serious disease of cabbage in Jammu and Kashmir. Amongst different inoculation methods tested, ‘Vein inoculation’ method gave quicker symptom expression and highest lesion progression followed by ‘Hydathode inoculation’ and ‘Clip inoculation’ methods, respectively. Spray inoculation for stomatal penetration of the pathogen failed to express any symptoms. Host range studies under conditions of artificial inoculation revealed that the bacterium infected almost all the crucifer crops cultivated in Kashmir, besides some cruciferous weeds but failed to infect any of the non-cruciferous plant species tested. Key words: Black rot, cabbage, host range, pathogenicity, Xanthomonas campestris pv. campestris <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Nazir A. Bhat et al. Pathogenicity and Host Range of Xanthomonas campestris pv. campestris – Incitant of Black Rot of Crucifers. J Phytol 2/10 (2010) 01-05.